Perilaku eksplorasi karier, dukungan sosial, dan keyakinan dalam pengambilan keputusan karier SMP - Rossallina, Lia; Salim, Romini Agoes (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2019)
AbstractMany SMP students choose mayor because of their good marks. They are not interested in that field, they just follow what their friend chooses, follow their teacher recommendation, or follow their parent’s advice, but not doing career exploration in the first. This research intended to examine the role of career exploration behavior in mediating social support and career decision making self-efficacy. Data collected from a student in grades 8 and 9 (n= 142), with convenient sampling techniques. The measuring used in this study were Carrier Decision Making Self Efficacy-SF, Adolescent Social Support Scale, and Career Exploration Survey, that have been adapted to Bahasa. Regression analysis and Sobel test showed that career exploration behavior significantly mediating the relationship between social support and career decision making self-efficacy. Social support from a parent, teacher, and friend is a trigger to emerge the career exploration behavior, which finally forms the career decision making self-efficacy. Implications, limitations, and suggestions are discussed.Keywords: Career decision making self-efficacy; Career exploration behavior; Junior high school student; Social support AbstrakBanyak siswa SMP memilih jurusan karena nilainya memadai di bidang tersebut. Padahal belum tentu sebetulnya ia berminat, mereka hanya mengikuti pilihan teman, menuruti rekomendasi gurunya, ataupun mengikuti saran orang tua, tanpa melakukan eksplorasi karier terlebih dahulu. Penelitian ini bertujuan menguji pengaruh perilaku eksplorasi karier dalam memediasi hubungan dukungan sosial dan keyakinan diri dalam pengambilan keputusan karier. Pengambilan data siswa kelas 8 dan 9 (n= 142), dengan teknik convenience sampling. Alat ukur yang digunakan adalah Carrer Decision Making Self Efficacy-SF, Adolescent Social Support Scale, dan Career Exploration Survey, yang sudah diadaptasi kedalam Bahasa Indonesia. Hasil uji regresi dan uji Sobel menunjukkan perilaku eksplorasi karier signifikan memediasi hubungan dukungan sosial dan keyakinan diri dalam pengambilan keputusan karier. Dukungan sosial yang diterima dari orang tua guru, dan teman adalah pemicu munculnya perilaku eksplorasi karier, yang akhirnya membentuk keyakinan diri dalam pengambilan keputusan karier. Implikasi, keterbatasan penelitian, dan saran untuk penelitian selanjutnya didiskusikan.Kata kunci: Dukungan sosial; Keyakinan diri dalam pengambilan keputusan karier; Perilaku eksplorasi karier; Siswa Sekolah Menengah Pertama